Implications of residue removal on soil quality in southwest Kansas - Ihde, Nicholas Adam (Kansas State University, 2011)
Through the 2007 Energy Independence and Security Act, the U.S. government has set goals to decrease fossil fuel use and sustainably produce ethanol from biomass, rather than existing corn grain-based ethanol. In southwest Kansas, crop residues are necessary to protect soil from erosion and to contribute to soil organic carbon (SOC) levels, a key factor in most desirable characteristics of soil quality, and are positively related to soil and crop productivity. Our objective was to quantify the effect of different residue management treatments (residue continuously retained, residue continuously removed, and alternating year residue removal) on soil physical properties, chemical properties, and corn yield. For 2.5 years, measurements and samples were collected from a Hugoton loam (L) and Bigbow fine sandy loam (FSL) in southwest Kansas. Residue continuously removed decreased water stable aggregates ≥ 0.25 mm and mean weight diameter of aggregates in contrast to residue continuously retained treatments following two winter seasons at the Bigbow FSL site. In residue continuously removed treatment for the Bigbow FSL, dry aggregate size distribution (ASD) measurements at the soil surface in the fine sandy loam had higher levels of soil % < 0.84 mm (wind erodible fraction) during the winter season of 2008-2009 and 2009-2010 by 6% and 15%, respectively. No significant differences in wet aggregate stability and ASD were measured at the Hugoton L site. Soil temperature and moisture levels monitored during the winter season showed a higher frequency of freeze-thaw cycles, which can be destructive to aggregates, in residue continuously removed plots. During the winter seasons of 2008-2009 and 2009-2010, the residue continuously removed treatments experienced three more freeze-thaw cycles than the residue continuously retained treatments in the Bigbow FSL soil. Bulk density measurements were variable, and no significant differences due to residue treatment were observed in both the loam and fine sandy loam. Total C, N, and exchangeable K were significantly different in residue continuously retained and removed plots due to residue treatment following 1 year of establishment of the study in the FSL. Total C was 14 g kg-1 and 8.7 g kg-1 in the residue continuously retained and removed treatments, respectively. Total N was 0.3 g kg-1 higher in the residue continuously retained versus the residue continuously removed treatment in the FSL. Irrigated continuous corn in southwest Kansas produces a lot of biomass, and has been reported to create emergence problems in the past. Corn emergence was slightly higher in residue continuously removed treatments in both the spring of 2009 and 2010, but differences were insignificant. No significant treatment effects on corn grain yield were observed in the duration of the study.
Keywords: soil quality southwest Kansas wind erosion; Agronomy (0285)